2003
DOI: 10.1002/cne.10728
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the relationship between astrocyte morphology and laminar boundaries in the molecular layer of adult dentate gyrus

Abstract: Astrocytes are known to play an integral role in the development of compartmental boundaries in the brain and in the creation of trauma-induced boundaries. However, the physical relationship between astrocytes and such boundaries in the adult brain is less clear. If astrocytes do respect or play an ongoing role in maintaining such boundaries, a correlation between the position of such a boundary and the morphology of neighboring astrocytes might be observable. In this study, we examined the distribution of ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 165 publications
2
28
0
Order By: Relevance
“…Data from dye-filling experiments suggest that protoplasmic astrocytic processes are initially fillopodial and later develop spatially segregated nonoverlapping domains (Bushong et al 2002(Bushong et al , 2003. Developmental changes in fibrous astrocytes are less well understood, but could, in principle, be studied using similar mechanisms.…”
Section: Postnatal Astrocyte Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from dye-filling experiments suggest that protoplasmic astrocytic processes are initially fillopodial and later develop spatially segregated nonoverlapping domains (Bushong et al 2002(Bushong et al , 2003. Developmental changes in fibrous astrocytes are less well understood, but could, in principle, be studied using similar mechanisms.…”
Section: Postnatal Astrocyte Maturationmentioning
confidence: 99%
“…Protoplasmic astrocytes populate the gray matter and have more irregular processes and few glial filaments (Vaughn and Pease 1967;Vaughn and Peters 1967;Bignami et al 1972;Freeman 2010). Protoplasmic astrocytes contact and sheathe synapses by extending thousands of thin processes, with typically only one or two in contact with blood vessels or CNS boundaries (Bushong et al 2002(Bushong et al , 2003Reichenbach et al 2010) Some have suggested that fibrous and protoplasmic astrocytes may be developmentally distinct (Fig. 1;Miller and Raff 1984;Nishiyama et al 2009).…”
mentioning
confidence: 99%
“…Intracellular injection of astrocytes in lightly fixed tissue slices was performed as described previously (Bushong et al, 2002(Bushong et al, , 2003. On day 4 after entorhinal cortex lesion, the mice were transcardially perfused with oxygenated Ringer's solution (0.79% NaCl, 0.038% KCl, 0.02% MgCl 2 ⅐6H 2 O, 0.018% Na 2 HPO 4 , 0.125% NaHCO 3 , 0.03% CaCl 2 ⅐2H 2 O, 0.2% dextrose, 0.02% xylocaine), followed by 4% paraformaldehyde in PBS, pH 7.4, for 8 -10 min, both at 37°C.…”
Section: Vimmentioning
confidence: 99%
“…These observations prompted a novel view on the physiological meaning of this tonic inhibition mediated by inhibitory A 1 receptors. In fact, astrocytes respond to neuronal activity with a time course considerably slower than neurons (tenths of seconds versus milliseconds; see Fellin et al, 2004) and promote broad volume transmission (reviewed in Halassa et al, 2007;Haydon and Carmignoto, 2006;Scemes and Giaume, 2006) thanks to their syncytium-like connectivity (D'Ambrosio et al, 1998;Latour et al, 2001;Wallraff et al, 2004) and to the number of synapses (near 10,000) contacted by each astrocyte (Bushong et al, 2003;Ventura and Harris, 1999). This means that astrocytic-derived adenosine can only be aimed at setting a global inhibitory tonus as a function of a timeaveraged activity in a broad neuronal circuit.…”
Section: Source Of Endogenous Extracellular Adenosinementioning
confidence: 99%